English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

(6x)x^5

(5/4)^-2

show work please

2006-10-25 08:44:48 · 6 answers · asked by yankee_914 1 in Science & Mathematics Mathematics

6 answers

(6x)x^5
6(x^1*x^5) <-- regroup
6x^(1+5) <-- add the exponents
6x^6

(5/4)^-2
(4/5)^2 <-- negative exponent, invert and make positive
16/25 <-- multiply through

2006-10-25 08:47:27 · answer #1 · answered by Puzzling 7 · 1 2

exponents are just the 'to the power of' symbols. e.g x^3 (^3 being to the power of 3) This just means that you multiply x by itself 3 times. So x^3 = x * x * x Now onto the sum. ((1/2)x)*(x^6)*((2y)^4) Break up the equation into two seperate sums. 1/2x*x^6 and (2y)^4 1/2x*x^6 = 1/2 * x * x * x * x * x * x * x = 1/2 * x^7 = 1/2x^7 (2y)^4 = 2^4 * y^4 = 2 * 2 * 2 * 2 * y * y * y * y = 16 * y^4 = 16y^4 The you put the simplified terms back together into an equation. 1/2x^7 * 16y^4 I hope that helped. I tried to explain the calculations, but it may not have been done very well.

2016-05-22 13:26:02 · answer #2 · answered by Anonymous · 0 0

6(x^6)

10^(-3) = (10^3)^(-1). That is the reciprocol of 10^3, and
multiplying by the reciprocol of 10^3 is the same as dividing by
10^3.

(5/4)^-2 = (5/4)^2(^-1).
1 / (25 / 4) = 0.16

2006-10-25 08:51:14 · answer #3 · answered by DanE 7 · 1 0

6x^6

(4/5)^2 = 16/25

2006-10-25 08:48:01 · answer #4 · answered by Dave 6 · 0 1

1.(6x)x^5
=6X^(1+5)
=6x^6

2.(5/4)^-2
=(4/5)^2
=16/25

2006-10-25 08:48:04 · answer #5 · answered by raj 7 · 0 2

How about I won't solve it?

I'll give you examples:

1.)
a * (a^n) = a^(n+1)
q * a * (a^n) = q*[a^(n+1)]
2.)
(a/b)^-n = (a^-n)/(b^-n) = [1/(a^n)]/[1/(b^n)] = (b^n)/(a^n)

If this doesn't help you, then re read the chapter. :)

Good luck

2006-10-25 08:53:50 · answer #6 · answered by Anonymous · 0 0

fedest.com, questions and answers